Permainan Tradisional Edang Tatong Sebagai Media Pembentukan Karakter Anak - Demon, Yohanes; Nagul, Wens; Lejap, Gracianus Edwin Tue P (Jayapangus Press, 2024)
Character is a trait that is inherent in every human being. Character formation can occur in various life processes. The process of character formation can be through traditional music games. Traditional games are cognitive symbols that are passed down from generation to generation. Forming character can strengthen an individual's identity and personality and directly develop a child's psychological aspects. Character formation aims to create a tough and strong personality in facing every situation and condition of children, especially the learning process. This research uses a descriptive qualitative approach with a phenomenological type of research. The data collection techniques used are observation, interviews, documentation. The technique for determining the research sample uses a purposive sampling technique. The data analysis techniques for this research are data reduction, data presentation, drawing conclusions. The results of the research prove that there are several character values ​​that emerge in the process of playing traditional Edang Tatong music which include the value of cooperation in the form of harmony in the process of playing the music. The value of creativity in the form of skills in processing the edang tatong musical instrument both individually and in groups. The value of unity appears in the form of comfort between one another as a group in the process of playing edang tatong music. Academic grades have an influence on increasing the learning motivation of Edang Tatong music players. The value of democracy refers to the freedom to play edang tatong music without translating it. Cultural awareness values ​​Refer to how to properly care for culture and history over time and introduce many people to existing cultural heritage. The conclusion of this research study states that the edang tatong music game is one of the most important media in the process of forming children's character.